Pancasila Law State as an Instrument of Indonesian Legal Politics: Efforts to Achieve a Just Indonesian Legal State - Putra, David Aprizon; Veronica, Nadia (Pancasila and Law Review, 2022)
Law exists to serve humanity, not the other way around. Therefore, legal systems must address human needs and ultimately achieve substantive justice. Pancasila, as a foundational ideology, embodies this principle, particularly through its second and fifth precepts, which emphasize justice as a core value. This normative juridical study employs two research methodologies: the statute approach and the historical approach. The data utilized in this study include secondary sources such as primary legal materials, secondary legal materials, and tertiary legal materials. Data processing involves three stages: data reduction, presentation, and verification. Law enforcement, particularly judges, play a crucial role in implementing and developing the legal framework of the Pancasila Law State, with a focus on social justice and addressing legal violations. Effective law enforcement should not be confined to strict legal procedures but should also embrace reasonableness. Legislators also play a vital role, as the legislative process is integral to the Pancasila Law State's fundamental structure, shaping the spirit of the regulations..